The functional assessment Berg Balance Scale is better capable of estimating fall risk in the elderly than the posturographic Balance Stability System A avaliação funcional Berg Balance Scale é capaz de estimar melhor o risco de quedas em idosos do que a posturografia Balance Stability System - Vanessa Vieira Pereira; Roberto Alcantara Maia; Sonia Maria Cesar de Azevedo Silva (Arquivos de Neuro-Psiquiatria)
The purpose of this study was to verify which instrument better identifies recurrent falls in the elderly. Ninety-eight old people, with an average age of 80±4 years, were submitted to an assessment of balance and fall risk by means of the Berg Balance Scale (BBS) and the posturographic Balance Stability System (BSS). The BBS was correlated with the BSS (r=-0.27; p=0.008), age (r=-0.38; p<0.001) and number of falls (r=-0.25; p=0.013) and the analysis of logistical regression showed that the elderly classified with fall risk on the BBS presented 2.5 (95%CI 1.08-5.78) more chance of identifying who had two falls or more over the last year. The BBS identified that the greater the age the worse the functional balance and demonstrated a greater capacity to identify falls risk suffered over the last year when compared with the BSS. A proposta do estudo foi verificar o instrumento que melhor identifica o risco de quedas recorrentes em idosos. O estudo incluiu 98 idosos, com média de idade de 80±4 anos, submetidos à avaliação do equilíbrio e risco de quedas por meio da Berg Balance Scale (BBS) e da posturografia Balance Stability System (BSS). A BBS foi correlacionada com a BSS (r=-0,27; p=0,008), com a idade (r=-0,38; p<0,001) e com o número de quedas (r=-0,25; p=0,013). A análise de regressão logística mostrou que idosos classificados com risco de quedas na BBS apresentaram 2,5 (95%IC 1,08-5,78) mais chances de identificar quem teve duas quedas ou mais no último ano. A BBS identificou que quanto maior a idade pior é o equilíbrio funcional e demonstrou maior capacidade de identificar o risco de quedas sofridas no último ano quando comparada a BSS.